The grain size effect on corrosion property of Al2Cr5Cu5Fe53Ni35 high-entropy alloy in marine environment. (November 2022) - Xue, L.; Ding, Y.; Pradeep, K.G.; Case, R.; Castaneda, H.; Paredes, M.
Abstract: The influence of grain size on the localized corrosion properties of a new high-entropy alloy (Al 2 Cr 5 Cu 5 Fe53 Ni35 ) in seawater is investigated in the present study. After Al 2 Cr 5 Cu 5 Fe53 Ni35 alloy undergoes cold rolling and annealing, its grain size will vary accordingly, resulting in different corrosion behaviors. The microstructural evolutions after different treated conditions are characterized by XRD, SEM, EDS and EBSD, whereas the corrosion properties are measured by potentiodynamic, potentiostatic and EIS experiments. The properties of the passive layer was studied with XPS and SIMS. The Point Defect Model approach is employed to analysis the data obtained from electrochemical experiments. The results show that by decreasing the grain size, the localized corrosion resistance of the material is enhanced. Highlights: A new high entropy alloy system is developed for marine applications with the corresponding anticorrosive properties expected for this adverse operating environment. Anticorrosive surface properties of the alloy are greatly improved by grain refinement through cold rolling and annealing processes. Combine 85% thickness reduction with 3 min annealing time period yields the best material corrosion resistance properties. This salient noble behavior of this material condition also prevails when subjected to different seawater concentration solutions herein studied.